Design and fabricate blanking die fir tensile test specimen - Wan Mohd Firdaus, Wan Sembak (2008)
The purposes of this project are to design and fabricate the blanking die. The blanking die will be uses for making the tensile test specimen. Tensile test specimen will be used for tensile test experiments. By producing it using blanking die, it can reduce the cost of purchasing and help student doing more experiments thus produced a better result from their experiments. During this project, an amount of tensile test specimen will be produced using the press tool technique. This project will followed few procedures include die designing, part fabricating and die troubleshoot. The tensile test specimen produced are with the standard dimensions ASTM and ISO standard that is equivalent to ASTM B557 and is suitable to be used by student for an experiment. The scope of the design will be base on 5 main areas, that is design the blanking die part/component using the CAD software, assemble the blanking die into hydraulic press machine that capable for 5 tones maximum, used the sheet metal from different type of material and thickness for blanking a tensile test specimen ( sheet metal materials will be aluminum, brass and stainless steel), evaluate the shear face and the fractured face on the tensile test specimen using the Image analyzer and indentified the breaking part of the tensile test specimen after tensile test specimen. The angle of the punch also will be evaluated. The blanking will be test into 4 main degrees that are 0 degree, 2 degree, 3 degree and 4 degree. With application of slanted punch, the blanking die able to cut thicker material up 3 mm. The fractured and sheared face also show some improvement during the evaluate process.